Housing prices and affordability among young people in Sungai Petani - Yushaini, Nur Anis Nabilah (2024)
In this academic project research explores the perception of housing prices and affordability among young peoples in Sungai Petani have been investigated. Through comprehensive data analysis and evaluation, the study aims to analyze the current housing market trends in Sungai Petani, focusing on prices and availability of housing units suitable for young peoples and to identify the factors that influence the affordability of young peoples to purchase a property. Therefore, this research is conducted as to investigate the conditions of property market that are affordable in Sungai Petani area. There are four main factors have been identified from the literature search such as location, income levels, market demand and supply, and government interventions are examined to provide insights into the current housing market trends and potential solutions. The researcher adopted quantitative approach in which a set of questions that consists 15 items excluding socio-demographic has been distributed using online survey. This research has gathered 131 responses, making it an acceptable for sampling size. Descriptive statistics were used in the data analysis process to obtain the results from the people who lived and want to purchase a property in Sungai Petani. Majority of the respondents agreed with the factors listed by the researchers. Various policies and strategies have been introduced by the government to increase homeownership among Malaysians. However, this issue has not been solved comprehensively until today.